Biolarvasides of Cananga odorata Flower and Zyzygium polyanthum Leaves Ethanol Extract on Aedes aegypti Larva - Nurlailah Nurlailah; Anny Thuraidah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Dengue hemorrhagic fever (DHF) is one of the diseases caused by Aedes Aegypti mosquitoes. DHF is still a public health problem, including in Indonesia, due to the high mortality rate caused by this mosquito. The risk caused by the bite of the Aedes sp mosquito is quite dangerous, including acute fever, bleeding, shock, and even death, so that efforts are needed to control it. One of the natural ingredients that can use to eradicate Aedes Aegypti mosquitoes without causing negative impacts on the environment is the Cananga flower and Zyzigium Leaves. This study purposes of determining the optimum concentration of Cananga Flowers and Zyzigium Leaves Ethanol extract of which was having biolarvaside effect to Aedes Aegypti larvae. The method used a simple experiment with Posttest Only With Control Group Design. The data result of the research analyzed with Logit and Wilcoxon test. Achievement of those tests was LC50 Zyzigium leaf extract on contact for 24 hours was 0.609-0.935, and LC99 was between 1.064-1.973 while Cananga flower extract obtained LC50 of 0.228-0.261 and the LC99 was 0.446 to 0.558. Wilcoxon test for compared bioalarvaside effect results between Cananga Flower and Zyzigium Leaf received a significance value less than α (0.001